The effects of mirabegron used for overactive bladder treatment on female sexual function: Mirabegron and female sexual function - Coguplugil, Adem Emrah; Bedir, Selahattin (Journal of Surgery and Medicine, 2023)
Background/Aim: Overactive bladder (OAB) is a common condition, especially in middle-aged women and can frequently have negative effects on female sexual function (FSD). The aim of the study was to assess the impact of mirabegron on female sexual dysfunction in women affected by OAB. Methods: In this cross-sectional study, 42 women with OAB and FSD were retrospectively enrolled. Patients were evaluated based on a detailed history, physical examination, uroflowmetry and residual urine measurements, 3-day voiding diary, visual analog scale (VAS), and Female Sexual Function Index (FSFI) questionnaire before and 12 weeks after treatment with mirabegron (50 mg/day). Results: At the 12-week follow-up, OAB symptoms improved significantly in all patients. The mean (standard deviation [SD]) FSFI total score significantly improved in 34/42 patients (80.9%) from 16.8 (1.3) to 26.9 (1.6); P<0.001. Mean (SD) scores significantly increased in domains of desire (from 2.1 [0.6] to 4.8 [0.2]), arousal (from 2.6 [0.3] to 4.3 [0.5]), lubrication (from 3.1 [0.6] to 4,1 [0.2]), orgasm (from 3.1 [0.2] to 4.3 [0.1]), and satisfaction (from 2.8 [0.4] to 4.1 [0.5]) after 12 weeks of treatment with mirabegron. Also, mean VAS scores significantly improved from 4.4 (1.4) to 8.8 (1.1); P<0.001. Conclusion: Treatment of OAB with mirabegron yields positive effects on sexual function of OAB patients.